Grit, Illness-Related Distress, and Psychosocial Outcomes in College Students With a Chronic Medical Condition: A Path Analysis. (12th December 2017) - Sharkey, Christina M; Bakula, Dana M; Baraldi, Amanda N; Perez, Megan N; Suorsa, Kristina I; Chaney, John M; Mullins, Larry L
Abstract: Objective: Adolescents and young adults (AYAs) with chronic medical conditions are at increased risk for a host of negative psychosocial outcomes, including depressive and anxious symptoms. Although studies have shown that illness appraisals (e.g., illness intrusiveness [II] and illness uncertainty [IU]) demonstrate consistent associations with such outcomes, few studies have examined positive factors that may relate to better psychosocial outcomes and appraisals. The present study evaluated grit (i.e., perseverance and passion for long-term goals), a novel construct in pediatric psychology, as a positive factor that relates to reduced untoward effects of II and IU on psychosocial outcomes in AYAs with chronic medical conditions. Methods: College students with a chronic medical condition ( N  = 120) completed questionnaires online, including measures of grit, II, IU, depression, anxiety, and emotional well-being (EWB). Results: The overall path analysis demonstrated that increased grit is directly associated with decreased depressive and anxious symptoms and increased EWB ( p  < .05). Further, analyses indicated that the positive association between grit and psychosocial outcomes is partially mediated by illness appraisals ( p  < .05). Conclusions: This study identified grit as a positive personal asset among AYAs with chronic medical conditions. By introducing a novel construct to the AYA literature, the study expands on the integration of positive psychology and pediatric psychology and underscores the need for greater research on the role of grit in chronic medical condition populations.